High-performance work systems, psychological empowerment, and power distance orientation in shaping employee innovation, a moderated mediation model - Miao Li; Rajah Rasiah (Scientific Reports)
Abstract This study examines the impact of High-Performance Work Systems on the Innovative Behavior of IT employees in China’s smartphone industry, drawing on Social Cognitive, Psychological Empowerment, and Social Information Processing Theories. Using a mixed-methods approach that combines Structural Equation Modeling and Fuzzy-Set Qualitative Comparative Analysis, this study is based on survey data from 481 full-time IT employees from leading smartphone companies in China. A moderated mediation model is developed to reveal how High-Performance Work Systems enhance employees’ perceptions of work meaning, competence, work impact, and self-determination, thereby fostering Innovative Behavior. Notably, Power-Distance Orientation moderates the relationship between High-Performance Work Systems and Innovative Behavior, particularly in terms of work meaning and competence. In high Power-Distance Orientation contexts, employees are more inclined to defer to authority, which reduces the motivational effect of High-Performance Work Systems on Innovative Behavior. The findings highlight the importance of optimizing human resource management practices to strengthen psychological empowerment, as a means of enhancing innovation and overall organizational performance. This study offers valuable practical implications for the highly competitive and rapidly evolving smartphone industry, providing insights into how organizations can effectively leverage High-Performance Work Systems to drive innovation.